ANALISIS HUBUNGAN EFEKTIVITAS DAN PERTUMBUHAN RETRIBUSI DAERAH SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (PAD) DALAM MENINGKATKAN KEMANDIRIAN FISKAL PEMERINTAH DAERAH KOTA JAMBI TAHUN 2020 - 2024 - Khairunnisa, Siti Nabilah; Hizazi, Achmad; Mansur, Fitrini (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the relationship between the effectiveness, growth, and contribution of regional retribution to Local Own-Source Revenue (PAD), as well as its implications for improving the fiscal independence of the Jambi City Government during the 2020–2024 period. The study employs a quantitative approach. The results show that the effectiveness level of regional retribution has declined from a very effective category in 2020 (110.55%) to ineffective in 2024 (53.78%). The growth of regional retribution is fluctuating and tends to be negative after 2021, with a significant decrease of up to -18% in 2024. The contribution of regional retribution to PAD is relatively low, ranging from 7.11% to 13.48%, and shows a declining trend. Meanwhile, the fiscal independence level of Jambi City remains in the low category, with a ratio of 22%–27%, reflecting a high dependence on transfer funds from the central government.